A medium for presumptive identification of Vibrio anguillarum. - Alsina, M (1994)
A medium (VAM) for differentiation of Vibrio anguillarum is described. The presence of bile salts, the high pH, and the high NaCl concentration select mainly for Vibrio species. The high salinity and the ampicillin select for a fraction of Vibrio species, and sorbitol fermentation differentiates among those vibrios still able to grow. One hundred ninety-seven of 227 strains of V. anguillarum were identified with this medium. Only 3 of 66 strains of Vibrio that were not V. anguillarum or V. anguillarum-like were recognized with this medium, and any of 7 non-Vibrio strains related to fish diseases or Escherichia coli grew on the medium. It is our contention that the medium described here constitutes an efficient instrument for presumptive detection of V. anguillarum in pathological and environmental samples.